ZIKV B-cell epitopes for immunodiagnostic tests - Kubiszeski, Janaina Rigotti; da Silva, David José Ferreira; Menezes, Gabriela de Lima; da Silva, Roosevelt Alves; Zini, Nathalia; Nogueira, Maurício Lacerda; Pena, Lindomar José; Piccoli, Julia Pinto; Cilli, Eduardo Maffud; da Silva, Joaquim Manoel; Bronzoni, Roberta Vieira de Morais (Elsevier, 2022)
The use of serological tests is valuable to diagnose Zika virus (ZIKV) infection and carry out epidemiological surveillance. However, ZIKV serological tests may result in false positives due to cross-reactivity between antibodies against other Flavivirus, especially dengue virus that worldwide disseminated. We used three online tools to predict amino acid sequences of B-cell epitopes. We selected and synthetized two epitopes that showed appropriate features in the molecular dynamic simulation and demonstrated to be suitable for serological assays.
Keywords: Arbovirus; Bioinformatics; Immunoassay; Peptide